Distribution pattern of ZO-1 and claudins in the epididymis of vampire bats. Issue 3 (2nd July 2020) - Castro, Mariana M.; Kim, Bongki; Games, Patrícia D.; Hill, Eric; Neves, Clóvis Andrade; Serrão, José Eduardo; Breton, Sylvie; Machado-Neves, Mariana
ABSTRACT: Epithelial cells connect with each other by tight junctions (TJs) in several tissues. In epididymides, TJs proteins form the blood-epididymis barrier (BEB), which is crucial for male fertility. However, little is known about BEB morphological and physiological aspects in wild animals. This study examines the region-specific distribution pattern of TJs proteins in D. rotundus' epididymis, assessing their regulation in rainy and dry season. The expression of zonula occludens-1 (ZO-1), and claudins (Cldn)-1, −3, and −4 were evaluated by confocal immunofluorescence and ELISA analysis. Herein, ZO-1 was strictly expressed in TJs, whereas Cldns were expressed in TJs and basolateral membranes of epithelial cells. Their co-localization and intensity of expression varied in the epididymal regions examined. The effect of season on protein expression was detected mainly in TJ proteins located in the proximal regions. As such, in the initial segment (IS), Cldn-3 and −4 were detected at low levels in basolateral membranes in the rainy season compared to the dry season. Furthermore, in the distal IS, Cldn-1 expression was lower in TJs of epithelial cells during the rainy season than the dry season. ZO-1 expression was higher in the cauda region than the corpus region by ELISA analysis. Additionally, in the corpus region, ZO-1 expression was higher in TJs during dry season compared to the rainy season. Our study sheds light on the understanding of BEB in D. rotundus, improving the knowledge of their reproductive biology.